Using Learningapps.org to Teach Descriptive Text Writing to Seventh Graders - Indriyani, Nina; Dwinalida, Khairunnisa (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
Writing is one of the productive skills that must be mastered by students learning English as a Foreign Language (EFL), especially Indonesian learners. However, many students still struggle with writing, resulting in low self-confidence. This research examines using the LearningApps.org website as a learning medium to teach students' writing skills, emphasising descriptive texts. The study used a quasi-experimental method with seventh graders at MTs Ma'arif NU 2 Cilongok Banyumas, with two groups of 44 students, the experimental and control classes. The data were gathered from pre- and posttests and then analysed using descriptive statistics, Mann-Whitney, and the N Gain test. According to the results, the experimental group, which utilised the LearningApps.org website, had a greater average posttest score (54.57) than the control group (43.33). In the Mann-Whitney test, the significance value is 0,005. The experimental group also had a greater N-gain percentage (34.09%) than the control group (11.08%). Although the results indicate that it is ineffective, the positive impact of using the LearningApps.org website is evident. These results suggest that the LearningApps.org website is a valuable and practical tool for supporting students' writing development in descriptive texts.